Childhood retinol-binding protein 4 (RBP4) levels predicting the 10-year risk of insulin resistance and metabolic syndrome: the BCAMS study - Ge Li; Issy C. Esangbedo; Lu Xu; Junling Fu; Lujiao Li; Dan Feng; Lanwen Han; Xinhua Xiao; Mingyao Li; Jie Mi; Ming Li; Shan Gao; et al. (Cardiovascular Diabetology, 2018)
Abstract Background Elevated retinol-binding protein 4 (RBP4) levels may contribute to the development of metabolic abnormalities, but prospective studies evaluating the association between childhood RBP4 levels and metabolic syndrome (MS) in adulthood are lacking. We investigated whether RBP4 levels during childhood predict cardiometabolic risk at 10-year follow-up. Methods The relationships between RBP4 levels, the established adipokines (leptin and adiponectin) and the components of MS were examined in 3445 school-aged children recruited in 2004 for the Beijing Child and Adolescent Metabolic Syndrome study. In 2015, 352 of these individuals completed an in-depth follow-up examination. Results Participants with higher childhood RBP4 levels had adverse cardiometabolic profiles at follow-up. Those with incident or persistent MS had higher baseline RBP4 levels than those who never exhibited the elements of MS. Moreover, baseline RBP4 predicted hyperglycemia (OR per SD increase = 1.48, P = 0.009), elevated triglyceride (OR = 1.54, P < 0.001), elevated blood pressures (OR = 1.46, P = 0.015), MS (OR = 1.68, P = 0.002) and insulin resistance (OR = 1.44, P = 0.015) in the 10-year follow-up phase, independent of baseline BMI. Significant improvements were seen for the net reclassification improvement and integrated discrimination index after adding childhood RBP4 levels into the risk models using conventional cardiometabolic risk factors in predicting MS at follow-up (P < 0.05). Leptin and adiponectin demonstrated the expected associations with metabolic disorders. Conclusions Childhood RBP4 serves as a risk factor for subsequent development of MS and its components, independent of pediatric obesity. Incorporating childhood RBP4 into conventional cardiometabolic risk assessment models significantly improves the prediction of MS.